Effects of vitamin D3 supplementation on strength of lower and upper extremities in athletes: an updated systematic review and meta-analysis of randomized controlled trials - Han, Qi; Xiang, Mai; An, Nan; Tan, Qiushi; Shao, Jing; Wang, Qirong (Frontiers in Nutrition, 2024)
Background: Coaches and athletes are increasingly interested in understanding athletes' serum vitamin D levels, their impact on strength, physical performance, and athletic outcomes.Previous meta-analyses were reported with limited sample size and no significant overall effect was found. Hence, it is crucial to conduct a thorough and up-to-date systematic examination and meta-analysis to elucidate the potential advantages of supplementing with vitamin D3 in enhancing muscle strength for athletes.We performed a thorough investigation, spanning three databases (PubMed, EBSCO, and Cochrane Library), seeking randomized controlled trials (RCTs) in all languages. These trials delved into the influence of vitamin D3 supplementation on the changes of pre-and postintervention muscle strength in healthy athletes. Our systematic examination and meta-analysis took into account serum 25(OH)D levels exceeding 30 ng/mL as a marker of adequacy.Results: Ten RCTs, comprising 354 athletes (185 in the vitamin D3 group and 169 in the placebo group), fulfilled the inclusion criteria. During the study, 36 athletes were lost to follow-up, leaving 318 athletes (166 in the vitamin D3 group and 152 in the placebo group) with documented complete results. In comparison with the placebo group, there is a significant increase between the changes of pre-and post-intervention serum 25(OH)D levels among athletes following a period of vitamin D3 supplementation (MD 14.76, 95% CI: 8.74 to 20.77, p < 0.0001). Overall effect of four strength measurements including handgrip, one repetition maximum Bench Press (1-RM BP), vertical jump, and quadriceps contraction was not significantly improved (SMD 0.18, 95% CI: -0.02 to 0.37, p = 0.08), but there was a significant increase in quadriceps contraction (SMD 0.57, 95% CI: 0.04 to 1.11, p = 0.04).Conclusions: This updated meta-analysis indicates the potential benefits of vitamin D supplementation for enhancing muscle strength in athletes when analyzing its quantitatively synthesized effects. With limited available studies for the quantitative synthesis, it cannot warrant significant overall enhancements in muscle strength when athletes attain adequate serum 25(OH)D levels through supplementation.